THE INFLUENCE OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS MEDIATING VARIABLE AT GIANYAR REGENCY CIVIL SERVICE POLICE UNIT - Lestari, Ni Putu Diva Sukma; Widyani, Anak Agung Dwi; Carina, Tiara (Jurnal Ekonomi Pembangunan STIE Muhammadiyah Palopo, 2024)
ABSTRACTEmployee performance is the result of the work of employees both in terms of quality and quantity in carrying out and completing the tasks. To increase employee performance, organizations must be able to provide motivation and satisfaction to their employees so that employees are increasingly encouraged to carry out their duties so that they can increase their overall productivity. This research aims to obtain empirical evidence of the influence of work motivation on employee performance with job satisfaction as mediating variable at the Gianyar Regency Civil Service Police Unit Office. The population in this study were all employees at the Gianyar Regency Civil Service Police Unit Office which consists of 67 employees. This study used census sampling technique. Data were collected with questionnaires. The data analysis technique uses SEM-PLS version 3.0. The research results show that motivation and job satisfaction have positive and significant effect on employee performance, motivation has positive and significant effect on job satisfaction, and job satisfaction mediates the influences of motivation on employee performance.Keywords: work motivation; job satisfaction; employee performanceABSTRAKKinerja karyawan merupakan hasil kerja karyawan baik dari segi kualitas maupun kuantitas dalam melaksanakan dan menyelesaikan tugas-tugasnya. Untuk meningkatkan kinerja karyawan, organisasi harus dapat memberikan motivasi dan kepuasan kepada karyawannya agar karyawan semakin terpacu dalam melaksanakan tugasnya sehingga dapat meningkatkan produktivitasnya secara keseluruhan. Penelitian ini bertujuan untuk memperoleh bukti empiris mengenai pengaruh motivasi kerja terhadap kinerja pegawai dengan kepuasan kerja sebagai variabel mediasi pada Kantor Satuan Polisi Pamong Praja Kabupaten Gianyar. Populasi dalam penelitian ini adalah seluruh pegawai di Kantor Satuan Polisi Pamong Praja Kabupaten Gianyar yang terdiri dari 67 orang pegawai. Penelitian ini menggunakan teknik pengambilan sampel sensus. Data dikumpulkan dengan kuesioner. Teknik analisis data menggunakan SEM-PLS versi 3.0. Hasil penelitian menunjukkan bahwa motivasi dan kepuasan kerja berpengaruh positif dan signifikan terhadap kinerja pegawai, motivasi berpengaruh positif dan signifikan terhadap kepuasan kerja, dan kepuasan kerja memediasi pengaruh motivasi terhadap kinerja pegawai.Kata kunci: motivasi kerja; kepuasan kerja; kinerja karyawan